Reformed theology today Practical-theological, missiological and ethical perspectives - P. Van der Walt, Sarel; Vorster, Nico (77fc6460-9d38-4709-bf07-ab531b471847, 2017)
This book is unique and of great importance for theologians from diverse traditions but who all share the relevance of the academic Reformed discourse. The book focuses on, and forms part of celebrating 500 years since the start of the Reformation during the 16th century. Its purpose is to commemorate the quincentenary anniversary of the Reformation in Europe and to indicate the way in which the rich legacy of this important period in the history of the church and society still influences globally the theological landscape in the fields of Practical Theology, Missiology and Ethics. Specific attention is given to the manner in which the core principles of the Reformation can be utilised for these disciplines and applied in a contemporary context. The Reformation changed the ecclesiastical landscape of the day and still provides the benchmark for theological principles and praxis in many Protestant denominations. This book illustrates and underscores the practical-theological legacy and importance of the Reformation for church and society. The collected works by various theologians reflect on the impact of Reformed Theology on their respective fields of expertise. The original research is based on literature studies and has not been published previously in any form. Its aim is to stimulate discourse in Theology and related disciplines. Although the chapters represent different perspectives, the collective aim is to propose the vast impact of the Reformational views as they relate to the current context. The target audience is Reformed theologians. This book focuses on ways in which the legacy of the Reformation addresses practical and relevant issues for 21st-century believers, scholars and churches. It explores inter alia important homiletical and liturgical aspects of the Reformation and contemplates the importance of continual reformation in this regard. Furthermore, it discusses a Reformed approach to apologetics, evaluates the driving forces behind the Reformation of the 16th century and its relevance to missions today as well as examines the sola Scriptura principle of the Reformation and provides a critical perspective on Prosperity Theology. Several pastoral themes take centre stage before various aspects of xenophobia and civil prejudice are being investigated - both being very relevant topics throughout the world today. The book also focuses on hermeneutics and ethics in a quest for a biblical ethical approach as well as congregational hymns in the Reformed churches of South Africa today. The research outcomes are relevant not only for the South African context, but also globally.